Perovskite/CIGS tandem solar cells: progressive advances from technical perspectives - Mohamad Noh M.F.; Arzaee N.A.; Fat C.C.; Sieh Kiong T.; Mat Teridi M.A.; Mahmood Zuhdi A.W. (Elsevier Ltd, 2025)
Tandem solar cells (TSCs) based on organic?inorganic halide perovskite have recently emerged as a new center of attraction. Among the wide array of preceding photovoltaic technologies, the industrially established copper?indium?gallium?selenide/sulfide (CIGS) solar cells offer greater advantages as bottom subcells for perovskite-based TSC. The controllable material composition of perovskite and CIGS allows for bandgap tuning close to the ideal values of double-junction TSC, enabling maximum photocurrent generation. Perovskite and CIGS solar cells also manifest high flexibility thanks to the thin-film nature of the devices, thereby widening their applicability in flexible and lightweight applications. With this motivation, this review systematically summarizes the technical progress of two-terminal (2T) and four-terminal (4T) perovskite/CIGS TSC development, whereby efficiencies of 24.2 % and 29.0 % have been demonstrated for the respective configurations. To understand how such performance reached up to this point, various key aspects such as conformal coating approaches, current matching, and transparent electrode materials are explained in further detail. The successful efforts in developing large-area minimodules on both rigid and flexible substrates are also elaborated. Overview on the technoeconomic and environmental parameters are also presented. From the comprehensive discussion, we analyzed the remaining challenges and posited further suggestions for future development directions of perovskite/CIGS TSC. ? 2023 Elsevier Ltd